A case report on intrapleural administration of antibiotic in tuberculous empyema - Bhushan, Aditya S.; B. L., Shashi Bhushan; R. , Anupama (International Journal of Advances in Medicine, 2023)
A 34-year-old male came with complaints of cough with copious yellowish expectoration, hemoptysis, difficulty in breathing and constitutional symptoms like fever, loss of weight and anorexia. Contrast enhanced computed tomography was done which showed left sided empyema likely secondary to rupture of left upper lobe lung abscess. The case was proceeded with fiber-optic bronchoscopy and bronchoalveolar lavage which showed narrowed bronchial openings on both sides. BAL analysis showed total cell count of 1500 cells/mm3 with 70% neutrophils, 5% lymphocytes and 25% of epithelial cells and macrophages. Culture showed Klebsiella species and antibiotics were escalated according to sensitivity pattern. Intercostal drain with under water seal was inserted on left side and thick pus was drained and sent for analysis. Anti-tubercular treatment was started. Due to persistent drainage of pus, intra pleural administration of Streptomycin was done for 30 days. Patient was monitored with serial chest X-rays and relevant blood investigations. Good clinicoradiological resolution was noted.